What Drives The Diffusion of AI Recruitment Systems in Swiss HRM? The Importance of Technological Expertise, Innovative Climate, Competitive Pressure, Employees’ Expectations and Contextual Factors - Revillod, Guillaume (International Journal of Engineering and Management Sciences, 2024)
This study examines organizational, environmental, and contextual factors influencing the diffusion of artificial intelligence recruitment systems in human resources management within Swiss organizations. Based on a survey provided to 324 private and public Swiss HR professionals, it explores how some technology-organization-environment theoretical framework predictors' as well as innovative climate provided by organizations influence the three stages – evaluation, adoption, and routinization – of diffusion of this innovation. To do this, the following article is based on a PLS-SEM structural equation model. Its main findings are that technological expertise, innovative climate, competitive pressure, and expectations regarding future use of the tool by organizations working in the same field are directly linked to the spread of this type of AI tool. However, public-sector organizations are more reluctant about using this type of tool. This aversion can, however, be moderated by an innovative climate and the fact that the HR function plays an active part in an organization's strategic direction. This said, this article makes a significant contribution to the literature about the diffusion of emerging technologies in organizations.